1999
DOI: 10.1095/biolreprod61.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Natriuretic Peptide System during Induced Ovarian Follicular Development in the Rat1

Abstract: All components of the natriuretic peptide (NP) system have been found in the ovary. The purpose of this study was to determine the hormonal regulation of the NP system during follicular growth and ovulation induced by gonadotropins eCG and hCG. Ovarian membrane binding, before and after treatment, revealed the presence of guanylyl cyclase-type receptors exclusively. Equine CG treatment increased Bmax from 225 +/- 50 fmol/mg protein in control animals to 354 +/- 51 fmol/mg protein, and additional hCG treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 40 publications
(52 reference statements)
2
33
0
Order By: Relevance
“…Measurement of cGMP concentration has already been described (Gutkowska et al 1999). Briefly, the dissected tissues were cut into small pieces and homogenized in 5 vol of ice-cold 5% (v/v) trichloroacetic acid (TCA).…”
Section: Ventricular Cgmp Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of cGMP concentration has already been described (Gutkowska et al 1999). Briefly, the dissected tissues were cut into small pieces and homogenized in 5 vol of ice-cold 5% (v/v) trichloroacetic acid (TCA).…”
Section: Ventricular Cgmp Assaymentioning
confidence: 99%
“…Because of their contribution to ANP and NO release in the cardiovascular system, estrogen and oxytocin receptors (OTR) were also evaluated (Gutkowska et al 1999, Jankowski et al 2001, Mukaddam-Daher et al 2001, Wang et al 2003). Our results demonstrate that cGMP concentration in the rat LV is controlled by both NOS and natriuretic peptides, but their inverse expressions at different stages of gestation suggest distinct roles in the control of physiologic cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…As well as the profound effects on endochondral ossification, these models of disrupted CNP/GC-B pathways suggest potentially important roles of this system in pituitary and gonadal tissues as Npr2 K/K mice are GH deficient and exhibit female infertility (Tamura et al 2004). Further support for CNP as a regulator of reproductive function comes from several studies that have shown CNP to potently stimulate cGMP production in GNRH neurons (Olcese et al 1994), pituitary gonadotrophs (McArdle et al 1993), and endocrine cells of the testis, ovaries, placenta and uterus (Khurana & Pandey 1993, Huang et al 1996, Middendorff et al 1996, Acuff et al 1997, Jankowski et al 1997, Gutkowska et al 1999, Stepan et al 2001, Walther & Stepan 2004, implicating CNP function at all levels of the hypothalamo-pituitarygonadal (HPG) axis. Furthermore, cGMP is a useful pharmacological target in the treatment of male reproductive disorders (Rosen & McKenna 2002, Christ & Hodges 2006.…”
Section: Introductionmentioning
confidence: 98%
“…Gene expression analysis and enzyme assays have indicated that other guanylyl cyclases are present at levels much lower than those of NPR2 . NPR2 is located throughout the granulosa cells of the follicle, in both the mural granulosa and the cumulus cells directly surrounding the oocyte; it is not expressed in the oocyte (Gutkowska et al, 1999;Zhang et al, 2010). The agonist of NPR2, C-type natriuretic peptide (CNP, released from a precursor protein that is encoded by the Nppc gene) is produced only in the mural granulosa cells (Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%